IMPLEMENTASI MEDIA INTERAKTIF PERMAINAN ULAR TANGGA DIGITAL DALAM PEMBELAJARAN TEKS ARTIKEL ILMIAH POPULER BAHASA INDONESIA KELAS VIII SMPN 6 CIMAHI - Nurfaturqi, M Ibnu; Natalia, Ade Lara; Utami, Atika Wiwi; Permana, Indra (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
This research aims to implement interactive media of digital snakes and ladders games in learning popular scientific article texts and assess its impact on student engagement and understanding. The background of this study is based on the low activity and motivation of students in participating in Indonesian language learning, especially in the material of popular scientific article texts which demand critical thinking skills and active communication. The research method used is qualitative descriptive with the subjects being students of class VIII E and VIII G at SMP Negeri 6 Cimahi. Data collection techniques were conducted through observation and questionnaires. The results showed that the use of digital snakes and ladders learning media significantly increased students' enthusiasm, learning spirit, and understanding of the material. Both classes showed positive responses to the learning media used, with good average scores in terms of enthusiasm, cooperation, understanding of the material, and a positive attitude. Although there are minor differences between the two classes in some aspects, in general, this media has proven effective in creating an interactive and meaningful learning atmosphere. Thus, digital snake and ladder game media can be an innovative alternative in Indonesian language learning that supports the development of 21st-century competencies.